Recent developments in capillary electrophoresis and capillary electrochromatography of peptides - Kasicka, Václav (Electrophoresis, 2006)
The article gives a comprehensive review on the recent developments in the applications of high-performance capillary electromigration methods, zone electrophoresis, isotachophoresis, isoelectric focusing, affinity electrophoresis, electrokinetic chromatography, and electrochromatography, to analysis, preparation, and physicochemical characterization of peptides. The article presents new approaches to the theoretical description and experimental verification of electromigration behavior of peptides, covers the methodological aspects of capillary electroseparations of peptides, such as rational selection of separation conditions, sample preparation, suppression of peptide adsorption, new developments in individual separation modes, and new designs of detection systems. Several types of applications of capillary electromigration methods to peptide analysis are presented: conventional qualitative and quantitative analysis, purity control, determination in biomatrices, monitoring of chemical and enzymatical reactions and physical changes, amino acid and sequence analysis, and peptide mapping of proteins. Some examples of micropreparative peptide separations are given and capabilities of capillary electromigration techniques to provide important physicochemical characteristics of peptides are demonstrated.
Keywords: Animals; chromatografie micelární elektrokinetická kapilární; Humans; lidé; peptidy; zvířata; Electrophoresis, Capillary; Peptides; elektroforéza kapilární; Chromatography, Micellar Electrokinetic Capillary